Two‐dimensional carbonitride MXenes: From synthesis to properties and applications - Weiwei Zhang; Shibo Li; Xiachen Fan; Xuejin Zhang; Shukai Fan; Guoping Bei (Carbon Energy)
Abstract Carbonitride MXenes, such as Ti3CNTx, Ti2C0.5N0.5Tx, and Ti4(C0.2N0.8)3Tx, have attracted much interest in the large family of two‐dimensional (2D) nanomaterials. Like their carbide MXene counterparts, the nanolayered structure and functional groups endow carbonitride MXenes with an attractive combination of physical and chemical properties. More interestingly, the replacement of C by N changes the lattice parameters and electron distribution of carbonitride MXenes due to the greater electronegativity of N as compared to C, thus resulting in significantly enhanced functional properties. This paper reviews the development of carbonitride MXenes, the preparation of 2D carbonitride MXenes, and the current understanding of the microstructure, electronic structure, and functional properties of carbonitride MXenes. In addition, applications, especially in energy storage, sensors, catalysts, electromagnetic wave shielding and absorption, fillers, and environmental and biomedical fields, are summarized. Finally, their current limitations and future opportunities are presented.